Improving Interpersonal Relationships through Interpersonal Communication - Intan Nirmalasari; Syifa Auliyah Rahma; Putri Lara Sati; Cholifia Sarining Pawasa (International Conference on Psychology and Education (ICPE), 2023)
Interpersonal relationships cannot be avoided in daily human activities, so it’s very important to build and improve to standardise the relationship between individuals and other individuals. Journal articles are made with the aim that the public will know more about how to improve interpersonal relations through building good interpersonal communication. The method used in this study is a qualitative research method with literature review. Based on the articles reviewed in this study, it shows that attentionhas not been maximised on how to improve interpersonal relationships through interpersonal communication. Whereas interpersonal communication acts in human interaction as a way to build or improve interpersonal relationships and at the same time as a way to develop the individual himself. Therefore, it is necessary to conduct further research on this matter.